Methimazole-Induced Cholestatic Jaundice: A Rare Case and Literature Review - Ahmed Mohamed Nefzi; Dhouha Cherif; Habiba Dabbebi; Haythem Yacoub; Hajer Hassine; Hela Kchir; Khadija Bellil; Nadia Maamouri (Journal of Investigative Medicine High Impact Case Reports)
Methimazole is commonly prescribed for patients with hyperthyroidism. It typically exhibits a well-tolerated profile, with common side effects including gastrointestinal disorders and rash. However, more serious rare yet adverse reactions, notably agranulocytosis and hepatotoxicity have been documented in literature. Here we present a case of a 27-year-old female, recently diagnosed with Graves’ disease, who was prescribed methimazole and developed severe pruritus with cholestatic jaundice 13 days later. Concomitant causes of liver disease were ruled out. The treatment was discontinued, and a switch to corticosteroid therapy with a regimen of radioactive iodine sessions was initiated. The patient’s condition showed a resolution of pruritus and jaundice, a disappearance of cytolysis with an aggravation of cholestasis followed by a gradual decrease, leading to the liver function normalization after 2 years. Methimazole-induced cholestatic jaundice is a rare yet severe adverse effect. Patients should be aware of this complication and advised to immediately stop taking the treatment when suggestive symptoms (pruritus, jaundice, dark urine, light-colored stool) occur.